Unveiling Idiom Usage: Analyzing Frequency and Context in Students' Diaries of Favorite Songof The 12th grade Students in Senior High School - Dian Ayu Ratnasari; Cicik Sophia, Theresia; Nur Ardini, Sukma (Papanda Journal of English Education, 2024)
The research aimed at identifying the frequency and context of the different idiomatic used diaries of fovorite song in the diary writing. It employed the theory of McCarty and O’Dell and an idiom dictionary to address the set research topics. This research employed qualitative descriptive research techniques. The data were gathered from students grade 12th. Then, they were analyzed by reducing and displaying information to draw conclusions. The result revealed that; 1) the six kinds of McCarty and O'Dell idiomatic idioms were discovered in the diaries: My Favorite Song. 2) the six categories of terms are Similes idioms (1%), Phrasal verb idioms (30%), Metaphorical idioms (32%), Aphorism idioms (30%), and Cultural and Historical idioms (7%). The most common form of idiomatic expression is a Fixed Statement idiom, which is the dominating idiom. On the other hand, simile idioms are the style of idiomatic expression that My Favorite Song. 3) the implied meaning of idiomatic can be deduced from the context of the statement in the diaries, idioms cannot be understood in just one word or phrase, so they must be understood as a whole in the context of one sentence or paragraph in order to understand the meaning of the original contextual. Therefore, it is suggested to the future researcher to enhance understanding of idiomatic expressions in English Department students, particularly through writing-by-writing diaries, by providing a valuable resource on frequency and contextual aspects. Keywords: Idiom, Frequency, Context, Diary Writing